Women in data : cutting-edge practitioners and their views on critical skills, background, and education - Lévy-Bencheton, Cornelia; Cutt, Shannon (O'Reilly Media, 2015)
Our new 2015 Edition of O'Reilly's Women in Data report reveals inspiring stories of success and insights from four women working in data, across the European Union. Now featuring a total of 19 interviews with women who are central to data businesses, authors Cornelia Lévy-Bencheton and Shannon Cutt uncover strategies for success for women in the field of data, and anyone interested in pursuing or advancing their career in data. While women are still an underrepresented minority in the disciplines of science, technology, engineering, and math (STEM), women in data and technology are no longer outliers. With this report, you'll learn how a remarkable group of women in data achieved their current level of success, what motivated them to get there, and their views about opportunities for women in the field. The stories in this book are inspiring, revealing insights that will widen the path for even more women in tech. These interviews explore: The expanding role of the contemporary data scientist New attitudes towards women in data among Millennials Benefits of the data and STEM fields as a career choice for women Remedies for closing the gender gap.